2014
DOI: 10.4271/2014-01-2375
|View full text |Cite
|
Sign up to set email alerts
|

Hydraulic Hybrid and Conventional Parcel Delivery Vehicles' Measured Laboratory Fuel Economy on Targeted Drive Cycles

Abstract: This research project compares laboratory-measured fuel economy of a medium-duty diesel powered hydraulic hybrid vehicle drivetrain to both a conventional diesel drivetrain and a conventional gasoline drivetrain in a typical commercial parcel delivery application. Vehicles in this study included a model year 2012 Freightliner P10HH hybrid compared to a 2012 conventional gasoline P100 and a 2012 conventional diesel parcel delivery van of similar specifications. Drive cycle analysis of 484 days of hybrid parcel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In contrast to the battery ESS, the hydraulic ESS has features of high power density, 10 low costs, and long lifespan. 11 So it has been widely applied to heavy-duty trucks and mobile machinery such as excavators and loaders (shown in Figure 1) for a long time.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In contrast to the battery ESS, the hydraulic ESS has features of high power density, 10 low costs, and long lifespan. 11 So it has been widely applied to heavy-duty trucks and mobile machinery such as excavators and loaders (shown in Figure 1) for a long time.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The MD trucks used in this research were a diesel conventional parcel delivery vehicle, a gasoline conventional parcel delivery vehicle, a diesel hybrid electric vehicle (HEV), and a diesel hydraulic electric vehicle (HHV). Specifications used as the basis for FASTSim modeling were sourced from NREL's Renewable Fuels and Lubricants (ReFUEL) Laboratory data captured during previous NREL field testing activities [2,3,4,5,6,7,8,9]. Table 1 details the key specifications for the four powertrain types examined in this study.…”
Section: The Fastsim Vehicle Modelmentioning
confidence: 99%
“…Recent research topics for power-split HHVs include different areas, such as dynamic analysis and controllers for passenger vehicles [21][22][23][24][25], experimental studies on hardware in the loop tests [26][27][28], concept car demonstrations, such as Hybrid Air by Peugeot [29], and system optimizations and optimal architecture studies for specific applications [10]. A recent study investigated the optimization system of a power-split HHV and reported energy savings up to 35% in comparison to a power-split hydrostatic transmission (HST) without considering engine management [30].…”
Section: Introductionmentioning
confidence: 99%